2016
DOI: 10.1159/000453059
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17RA Promotes Humoral Responses and Glomerular Injury in Experimental Rapidly Progressive Glomerulonephritis

Abstract: Background/Aims: Interleukin (IL)-17A and IL-17F are proinflammatory cytokines, which signal through a receptor complex consisting of IL-17RA and IL-17RC subunits. We sought to define the role of IL-17RA expression by leukocytes and stromal cells in nephritogenic immunity and injury in experimental glomerulonephritis. Methods: Glomerulonephritis was induced in wild-type and IL-17RA-deficient (IL-17RA-/-) mice by sheep anti-mouse glomerular basement membrane globulin. Renal injury and immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…In recent years IL-17A and, to lesser degree, IL-17F and IL-17RA have been identified as important proinflammatory regulators and potential therapeutic targets in autoimmune and inflammatory kidney diseases, including human and experimental crescentic GN. [6][7][8][25][26][27][28] However, the potential function of other IL-17 cytokines and IL-17 receptors is still unclear. We measured serum protein levels of the IL-17 cytokine family members in 70 patients with ANCA-associated GN, the most common form of crescentic GN.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years IL-17A and, to lesser degree, IL-17F and IL-17RA have been identified as important proinflammatory regulators and potential therapeutic targets in autoimmune and inflammatory kidney diseases, including human and experimental crescentic GN. [6][7][8][25][26][27][28] However, the potential function of other IL-17 cytokines and IL-17 receptors is still unclear. We measured serum protein levels of the IL-17 cytokine family members in 70 patients with ANCA-associated GN, the most common form of crescentic GN.…”
Section: Discussionmentioning
confidence: 99%
“…The Th17/IL-17 axis participates in the production of autoantibodies by B cells, as demonstrated in studies with autoimmune models in which the IL-17 drives the development of autoreactive germinal center (GC); and mice lacking the IL-17 receptor have reduced B cell development and humoral responses (229,230). In another study with an autoimmune disease model, the blockade of IL-17 signaling was associated with a significant reduction in both the number and size of germinal centers (231).…”
Section: Production Of Autoantibodiesmentioning
confidence: 99%
“…76 IL-17 seems to be involved in autoimmune glomerulonephritis. 77,78 It has been suggested that IL-17R-knockout mice were protected from crescent formation but not from glomerular necrosis or renal interstitial injury. 77,78 The role of other IL-17 cytokine family members and their receptors in inflammatory nephropathies remains unclear.…”
Section: Il-17mentioning
confidence: 99%